Grades, Student Satisfaction and Retention in Online and Face-to-Face Introductory Psychology Units: A Test of Equivalency Theory - Garratt-Reed, David; Roberts, Lynne D.; Heritage, Brody (Frontiers in Psychology, 2016)
There has been a recent rapid growth in the number of psychology courses offered online through institutions of higher education. The American Psychological Association (APA) has highlighted the importance of ensuring the effectiveness of online psychology courses. Despite this, there have been inconsistent findings regarding student grades, satisfaction, and retention in online psychology units. Equivalency Theory posits that online and classroom-based learners will attain equivalent learning outcomes when equivalent learning experiences are provided. We present a case study of an online introductory psychology unit designed to provide equivalent learning experiences to the pre-existing face-to-face version of the unit. Academic performance, student feedback, and retention data from 866 Australian undergraduate psychology students were examined to assess whether the online unit produced comparable outcomes to the ‘traditional’ unit delivered face-to-face. Student grades did not significantly differ between modes of delivery, except for a group-work based assessment where online students performed more poorly. Student satisfaction was generally high in both modes of the unit, with group-work the key source of dissatisfaction in the online unit. The results provide partial support for Equivalency Theory. The group-work based assessment did not provide an equivalent learning experience for students in the online unit highlighting the need for further research to determine effective methods of engaging students in online group activities. Consistent with previous research, retention rates were significantly lower in the online unit, indicating the need to develop effective strategies to increase online retention rates. While this study demonstrates successes in presenting online students with an equivalent learning experience, we recommend that future research investigates means of successfully facilitating collaborative group-work assessment, and explores factors other than non-equivalence of learning experiences that contribute to student retention in online units.